INFLUENCE OF SOIL ON ALPHA DIVERSITY AND VEGETATION STRUCTURE IN FORESTS ALONG IQUITOS - NAUTA ROAD, PERU - VALLES PÉREZ, Luis Andrés (2022)
Soil is the superficial part of the earth where plants grow, among them, species of economic importance that provide food, medicine and wood for local people, however, little has been studied about the influence of the soil on the plants in the Amazon Peruvian. Due to these reasons, the relationship between the physical-chemical characteristics of the soil and the diversity and structure in the forests in the area of the Iquitos-Nauta highway, Loreto, Peru, was evaluated. 102 pits for soil sampling and 37 plots of 50 x 20 m for vegetation study, were settled. Spearman's correlation index indicated that alpha diversity is negatively related to cation exchange capacity, potassium, phosphorus, and organic matter; and the structure (number of individuals) is negatively related to the amount of clay and pH. In conclusion, the alpha diversity and structure of the vegetation is determined by the physical-chemical characteristics of the soil.